2011
DOI: 10.1111/j.1365-3059.2011.02465.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of monilia disease caused by Monilinia linhartiana on quince in southern Spain

Abstract: This study elucidates the aetiology and epidemiology of monilia disease of quince caused by the fungus Monilinia linhartiana in Spain. Disease incidence and the dynamics of apothecial development and ascospore discharge were quantified and the pathogen was characterized using morphological and molecular methods. The pathogen did not produce conidia or apothecia on agar media but produced conidia on leaves showing symptoms and apothecia on mummified young quince fruit. Monilinia linhartiana was not pathogenic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a study conducted by Ürey (2012), it was determined that approximately 40% of different quince orchards in Edirne had Monilia disease. Similarly, in another study carried out in Spain, Monilinia linhartiana was stated to be the common mold type in quince orchards (Moral et al, 2011). The fact that Monilinia genus could not be isolated in this study shows that an effective protection method is applied against this species in quince orchards.…”
mentioning
confidence: 43%
“…In a study conducted by Ürey (2012), it was determined that approximately 40% of different quince orchards in Edirne had Monilia disease. Similarly, in another study carried out in Spain, Monilinia linhartiana was stated to be the common mold type in quince orchards (Moral et al, 2011). The fact that Monilinia genus could not be isolated in this study shows that an effective protection method is applied against this species in quince orchards.…”
mentioning
confidence: 43%
“…1) causing blossom blight of flowers, brown rot on fruits, canker and gummosis of tree trunk (Yildiz and Ozkilinc, 2021). M. linhartiana [Saccardo, P.A., 1883] (Table 2) was reported to infect mainly the quince (Cydonia oblonga) (Moral et al, 2011;Martini et al, 2014;Lantos and Petróczy, 2016) (Fig. 1.B).…”
Section: Introductionmentioning
confidence: 99%
“…genetically. E.g., an ITS1-5.8S-ITS2 analysis (Moral et al, 2011) indicated a strict host plant preference and plantpathogen interactions (Gullner and Kömives, 2001;Szabó et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these fungi are well-known plant pathogens: B. cinerea has been detected and isolated from C. japonica in Sweden [ 5 , 16 ], Lithuania [ 17 ], and Russia [ 18 ]; Monilinia fructigena was found on C. japonica fruits in the Moscow region [ 18 ] and Sweden [ 16 ]; M . cydonia has been found to damage flowers in Russia [ 18 ], and M. linhartiana was found to be the pathogen responsible for fruit rot of Cydonia oblonga in Spain [ 19 ].…”
Section: Introductionmentioning
confidence: 99%